State of the World's Cities bridging the urban divide - UN Habitat (Nairobi UN HABITAT, 2008)
The world's urban population now exceeds the world's rural population. What does this mean for the state of our cities, given the strain this global demographic shift is placing upon current urban infrastructure?. Following on from previous State of the World's Cities reports, this edition uses the framework of 'The Urban Divide' to analyse the complex social, political, economic and cultural dynamics of urban environments. The book focuses on the concept of the 'right to the city' and ways in which many urban dwellers are excluded from the advantages of city life, using the framework to explore links among poverty, inequality, slum formation and economic growth. The volume will be essential reading for all professionals and policymakers in the field, and a valuable resource for researchers and students in all aspects of urban development.
Includes Index
Keywords: Cities and towns, Urban Environment, Urban Areas